Use of clobetasole propionate in patients with scalp psoriasis – own experience - Zawirska, Agnieszka; Kubisiak-Michalska, Alina; Adamski, Zygmunt (Dermatology Review/Przegląd Dermatologiczny, 2010)
Introduction. Therapy of scalp psoriasis is a big problem. Treatment modalities used so far are not always efficacious and also not fully satisfactory to the majority of patients. Objective. Evaluation of efficacy and safety of shampoo containing clobetasole propionate in patients with scalp psoriasis. Material and methods. The study was performed on 29 patients hospitalised in the Dermatology Department of Poznan Regional Hospital. Shampoo containing 0.05% of clobetasole propionate was applied to the scalp once daily for 4 weeks. Analysis of erythema, scaling and infiltration as well as percentage of scalp involvement was performed every 7 days. Results. Improvement was achieved in all patients. After 4 weeks of treatment we noticed a decrease of scalp involvement from 45 to 5%. The global improvement was assessed as 2.9 by the doctor and 2.8 points by patients on a 3-grade scale. We also observed a significant decrease of pruritus. No side effects were noticed. Conclusions. Shampoo with clobetasole propionate is not only efficacious, but also safe and well tolerated.